OPTIMIZATION OF BIOSURFACTANT PRODUCTION BY ENCAPSULATED OF BACILLUS SP. F7 CELLS USING RESPONSE SURFACE METHODOLOGY (RSM) - Mutiara Prastianti, Fadia
Biosurfactant popularity is increasing due to the shift in the use of surfactants to biosurfactants in several industries so the demand for biosurfactants increases and the production of biosurfactants needs to be increased. Bacillus sp. F7 has the ability to produce biosurfactants with good surface activity, but large-scale production requires high costs due to low cell productivity. Cell immobilization using calcium alginate can be applied to increase cell productivity in producing biosurfactants. Calcium alginate has limitations in the low ability of the matrix to maintain cell number during cycle production and nutrient diffusion limitation. Therefore, this study aims to optimize the factors affecting immobilized cell viability, compare their biosurfactant productivity between immobilized cells and free cells, determine the stability of the beads in the biosurfactant production cycle, and determine the shelf life of the beads during storage. Biosurfactant production is carried out in a batch system using Stone Mineral Salt Solution (SMSS) medium at pH 7.0, incubated at 50ºC, 150 rpm. Optimization of cell immobilization was carried out using RSM with Central Composite Design (CCD) by targeting the maximum number of cells in the beads after 88 hours of incubation. The variables that were optimized included alginate pH, bead size, and alginate volume with the cell suspension volume kept constant at 5 mL at a cell density of 108 CFU/ml. The results showed that beads with a 9.77 mL alginate volume, pH of 7.06, and a 5.3 mm bead size could maintain a high cell count at 108 CFU/ml with higher productivity than free cells. Alginate beads were stable in biosurfactant production for up to 6 production cycles with a total biosurfactant of 0.933 g/L. Cell viability remained stable during 28 days at refrigerated storage. It can be concluded that beads have high stability in maintaining cell viability with high productivity.